Reliability and optimization of structural systems proceedings of the sixth IFIP WG7.5 working conference on reliability and optimization of structural systems, 1994 - Rackwitz, R.; Augusti, Guiliano; Borri, Antonio (Chapman & Hall, 1995)
The 6th meeting sponsored by IFIP Working Group 7.5, on reliability and optimization of structural systems, took place in September 1994 in Assisi, Italy. This book contains the papers presented at the working conference including topics such as reliability of special structures, fatigue, failure modes and time-variant systems reliability.